The Role Of Abu Mansur Al-Maturidi’s Teachers In His Development as A Scholar Of Theology - Usmonov Iskandar Foziljonovich (Penerbit Jurnal Indonesia, 2024)
This article provides information about the teachers of Imam Maturidi, their contributions to the formation of theological science, and the development of his ideas.